Investigation on Students Feedback about Distance Learning for Art Subject - Daulay, Muhammad Cahya; Kusumawardhani, Mega Iranti (ULTIMART Jurnal Komunikasi Visual, 2023)
The utilization of online platforms for learning has become increasingly common, although it is still relatively unexplored in specific disciplines such as Art and Design. In the Film and Animation Majors within the Art and Design Faculty, students encounter subjects that necessitate the development of technical proficiency in their learning outcomes and subjects that require in-person discussions to deepen their understanding. Gaining technical proficiency typically requires practical, hands-on practice, which is most effectively facilitated through in-person instruction. This article presents the feedback received from students enrolled in two foundation classes, one practical and one theoretical, regarding their experience with distance learning. The authors collected and analyzed feedback from both types of classes, focusing on participants who provided feedback for both practical and theoretical courses. The outcomes consist of recommendations from the students' perspectives, highlighting the successes and challenges encountered with distance learning in the respective classes. Keywords: distance learning; film; animation; major; technical proficiency skill; online learning.